Assesment Fungsi Kognitif pada Anak dengan Penyakit Kronik - Rachmawati, Anita; Allenidekania, Allenidekania; Agustini, Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify what assessments can be used to screen cognitive function in children with chronic illnesses. The method used is a systematic review using the PRISMA flow diagram. Researchers used PIOs and searched for English language articles published from 2013 to October 2023. The databases used were PubMed, ProQuest, Science Direct, Taylor & Francis, Scopus, and EBSCO Medline. This systematic review showed that the initial total of articles obtained from all databases was 5889. After limiting the articles, 297 articles were obtained, which were then screened according to the inclusion criteria, with the final result being eight articles with a cross-sectional design. In conclusion, four instruments for assessing cognitive function in children with chronic diseases include Ouvrier modified MMSE, EpiTrack Junior (EpitrackJR), pedsFACIT-PCF, and Ped-ANAM. The Ouvrier-modified MMSE is widely used in several kinds of literature and is validated against standard cognitive function examinations by examination. Keywords: Children with Chronic Diseases, Assessment, Cognitive Function